2016
DOI: 10.1016/j.autrev.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of IL-17 in vitiligo: A review

Abstract: IL-17 is involved in the pathogenesis of several autoimmune diseases, however its role in vitiligo has not been well defined. Emerging human and mouse studies have demonstrated that systemic, tissue, and cellular levels of IL-17 are elevated in vitiligo. Many studies have also shown significant positive correlations between these levels and disease activity, extent, and severity. Treatments that improve vitiligo, such as ultraviolet B phototherapy, also modulate IL-17 levels. This review synthesizes our curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 85 publications
1
101
1
5
Order By: Relevance
“…Interestingly, IL‐17 expression was also evaluated either in situ or in periphery. Contrasting with most studies, transcripts of IL‐17 were not detected in vitiligo biopsies (data not shown) and serum levels of IL‐17 were not increased in patients (Fig. b).…”
Section: Epidemiological and Clinical Features Of Vitiligo Patientscontrasting
confidence: 77%
“…Interestingly, IL‐17 expression was also evaluated either in situ or in periphery. Contrasting with most studies, transcripts of IL‐17 were not detected in vitiligo biopsies (data not shown) and serum levels of IL‐17 were not increased in patients (Fig. b).…”
Section: Epidemiological and Clinical Features Of Vitiligo Patientscontrasting
confidence: 77%
“…Several human studies have investigated the roles that Th17 cells play in vitiligo, demonstrating an increased frequency of circulating Th17 cells and elevated serum levels of IL‐17 that positively correlates with disease duration, extent, and severity of disease …”
Section: Il‐17 and Autoimmune Skin Diseasesmentioning
confidence: 99%
“…T regulatory cells are involved in downregulation of immune response, thereby showing their importance in limiting the progression of this disease . There are many studies which have supported the role of cytokines in various inflammatory and autoimmune disorders . Previous studies have shown increased serum levels of proinflammatory cytokines like IL‐17A, IL‐1β, and also TGF‐β in vitiligo patients.…”
Section: Introductionmentioning
confidence: 99%